Mandibular reconstruction. (February 2018) - Kakarala, Kiran; Shnayder, Yelizaveta; Tsue, Terance T.; Girod, Douglas A.
Highlights: Mandible reconstruction is most often optimized using an osseous free flap. Virtual surgical planning is utilized to improve operative efficiency and outcomes. Mandible tissue engineering remains a promising but uncommonly used technique. Research into outcomes, cost, and value must inform future surgical innovation. Abstract: Mandibular reconstruction presents unique functional and aesthetic challenges to the reconstructive surgeon. This review will cover current techniques for mandibular reconstruction, including the various plating strategies for rigid fixation, the choice of osseous donor site, and the concurrent reconstruction of associated soft tissue defects. Recent developments and future horizons in mandibular reconstruction including the use of virtual surgical planning and tissue engineering will also be addressed.